Abdominopelvic actinomycosis: An unexpected diagnosis in an elderly female with a destructive-appearing soft tissue mass. (2022) - Hyser, Elise; Antala, Drashti; Friedman, Harvey; Stake, Jonathan
Abstract: We present the case of an elderly female who underwent a workup for acute blood loss anemia that incidentally led to the discovery of abdominopelvic actinomycosis. While esophagogastroduodenoscopy and colonoscopy were unremarkable, CT abdomen/pelvis displayed a soft tissue mass in the left sacral ala and presacral area that appeared suspicious for malignancy. MRI pelvis revealed a presacral abscess, and an IR-guided biopsy cemented the diagnosis. This case exemplifies how actinomycosis can mimic the presentation of cancer. Risk factors included a history of ischemic colitis and lumbar laminectomy, as mucosal tissue compromise and orthopedic hardware can be niduses for infection.